Using social software to enhance the student e-learning experiences and activities in higher education - Negas, Mário Carrilho (2014)
E-learning – almost by definition - uses advanced technologies to support the formation and development of students. Therefore, Web 2.0 applications have merged into the e-learning domain. Learning experiences in modern e-learning include collaborative aspects and active contributions to learning content. Thus, an e-learning using social network tools arises as a potential learning method. So, it should be questioned if the Web 2.0 applications, used in social networks, can play a positive role in e-learning, as long as professors give them the optimal use and students interpret them as didactic tools. For this purpose, the present paper gives give a consolidated review on how the concept of social networks has influenced e-learning communities. In conclusion, the paper argues that the pedagogical potential of social software can perform the ability to create awareness between students, sharing information and resources that are originally developed for themselves, but made available to others.